Foreign body aspiration leading to complete lung collapse due to left bronchus obstruction: A Case Report - Teimouri, Mahtab; Moradi, Muhammadhosein; Ansari, Sara; Teimouri, Maryam; Jafari, Ebrahim (Student Research in Translational Medicine, 2020)
Foreign body aspiration(FBA) is a common life-threatening condition in pediatric emergency medicine that can lead to airway obstruction, asphyxia, and severe respiratory distress. An 18-month old female infant referred with the complaint of dry cough and wheezing with a sudden onset of dyspnea. At the time of admission, her oxygen saturation was 89%. Chest X-ray (CXR) showed a significant opacity in the left lung and the mediastinum shifting to the left side. Complete collapse seen in the left lung was associated with consolidation in the residual lung parenchyma. Rigid bronchoscopy revealed the corn kernels, which were taken out accordingly. The air trapped in the involved lung parenchyma was absorbed, and signs of shrinkage and collapse as consequences of the obstruction occurred in distal parts of the obstruction point. An emergent therapeutic decision is crucial in the early stages of management.